Determination of naphthenic acids in crude oils using nonaqueous ion exchange solid-phase - Jones,DM; Watson,JS; Meredith,W; Chen,M; Bennett,B (Analytical Chemistry, 2001)
A method is presented for the routine, rapid, and quantitative analysis of aliphatic and naphthenic acids in crude oils, based on their isolation using nonaqueous ion exchange solid-phase extraction cartridges. The isolated acid fractions are methylated and analyzed by gas chromatography and gas chromatography/mass spectrometry. The method is effective on both light and heavy oils and is capable of providing mechanistic information of geochemical significance on the origin of the acids in the oils. Analysis of oils that were solvent extracted from laboratory and field mesocosm marine sediment oil degradation studies indicate that this new method of analyzing the products of hydrocarbon biodegradation may be a useful tool for monitoring the progress of bioremediation of oil spills in the environment.